A study of photometric observations of (3200) phaethon from Lulin Observatory. (December 2020) - Lin, Zhong-Yi; Yoshida, Fumi; Lin, Yi-Chuan; Cheng, Chung-Chien; Ip, Wing-Huen; Cheng, Yu-Chi; Pan, Kang-Shian; Daisuke, Kinoshita; Chi, Hsin-Chang
Abstract: The near-Earth asteroid (3200) Phaethon is regarded as the parent body of the Geminid meteor stream. It is also an active asteroid with a very blue spectrum which is similar to that of the members of the Pallas family. For obtaining this asteroid's surface property in more detail, we conducted a series of multicolor photometry of this asteroid over a wide range of solar phase angle during its close approach to the Earth in the end of 2017. Our observations confirmed that Phaethon is a C-complex asteroid as previous studies have claimed. We also obtained the phase curve for this asteroid in solar phase angle of 22.67 ∼ 114.48°. From this result, we estimate that the absolute magnitude (H) of this asteroid is 14.450 ± 0.017 mag, and its phase slope is ( β ) ∼0.0422 ± 0.0005. Using the absolute magnitude that we estimated, together with an estimate of Phaethon's albedo (0.122 ± 0.03) that previous literature derived, we can derived the Phaethon's diameter, 4. 90 − 0.54 + 0.79 km. The diameter estimate is roughly consistent with what was observed through the radar ranging measurement conducted as the same period as our observation. Highlights: Improving the cited references throughout the paper. Improving the form of the formula and estimated diameter used throughout the paper. Remove author statement in the top of the paper. Re-edit the section number (2. Observations 3. Results). Rewrite all the figure captions because of the grammar. Simplified the discussion part but did not change the main results from the the paper.